In situ fluorescence labelling of jasmonic acid binding sites in plant tissues with cadmium‐free quantum dots. Issue 1 (1st February 2015) - Liao, Qiumei; Yu, Ying; Cao, Yujuan; Lin, Bixia; Wei, Jingjing
Abstract : The fluorescence labelling of plant hormone binding sites is an important analytical technique in research on the molecular mechanisms of plant hormone activities. The authors synthesised a jasmonic acid (JA)‐conjugated ZnS:Mn quantum dot (QD) probe, with a cubic structure and average hydrodynamic sizes of about 17.0 nm. The maximum fluorescence emission of the probe was recorded at about 585 nm. The probe was used for fluorescence labelling of JA binding sites in mung bean seedling tissues. Analysis revealed that the probe exhibited high selectivity to JA binding sites and good performance in eliminating interference from background fluorescence in plant tissues. In addition, the probe did not exhibit any apparent biotoxicity, and is much more suitable than probes constructed from CdTe QDs for the analysis of biological samples.